Clinically significant drug-drug interactions in the treatment of cardiovascular diseases on hospital admission - Drndarević, Aneta; Draganov, Ivana; Miljković, Branislava; Cvijanović, Dane; Davidović, Aleksandar; Savković, Tatjana; Vezmar Kovačević, Sandra (Archives of Pharmacy, 2022)
Clinically significant drug-drug interactions (DDIs) are expected in patients with cardiovascular diseases due to the number of drugs in therapy. The aim of the research was to analyze DDIs during treatment which preceeded the admission to the cardiology department. In the cardiology department of the Clinical Hospital Center Zvezdara, the treatment of patients with ≥2 drugs before admission was analyzed. DDIs were identified using the Lexicomp database (Lexi-Interact). Data were analyzed descriptively and with linear regression analysis. During research, out of 132 participants 88.6% had ≥1, while 41.7% had ≥5 DDIs. The total number of DDIs was 648 (median 3, range 0-19). Men constituted 64.4% of the population, with a median age of 70 years (32-90). Patients had 4 diagnoses (1-13) and 6 medications on admission (2-15). In 3.8% of patients, contraindicated DDIs of anticholinergics were observed,  23.5% had DDIs that required caution or a change in therapy, while interactions requiring follow-up were observed in 86.4% of patients. Angiotensin-converting enzyme inhibitors (30.4%), acetylsalicylic acid (26.6%) and loop diuretics (16.5%) were most frequently involved in DDIs, while the most common adverse events could be renal failure (21.5%), hypotension 19.7%) and bleeding (13.7%). The number of drugs in therapy was a predictor of DDIs (p